(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The aim of the current study is to shed light on the role played by e-learning in the Republic of Iraq and the most important challenges facing this type of emerging research. Additionally, the study examines the extent of effectiveness in e-learning, particularly in light of the outbreak of the Corona virus pandemic (COVID-19), from the lens of teaching faculty engaging in e-learning as well as its challenges and perceived effectives as experienced by students. The research sample consisted of professors and students from different Iraqi universities who engaged in this form of online education. A descriptive approach was adopted to analyze the data gathered for the research. From our findings, a number of recommendations emerged including how e-learning has a positive impact on the educational experiences of the teaching staff as well as students. It is therefore imperative to embrace education technology to the extent possible in the context of Iraq, through the use of the most advanced software and equipment available in our effort to improve and expand the e-learning process. The majority of the obstacles to e-learning in Iraq are rooted in slow internet speed and unremitting power outages. Despite these difficulties, both teachers and students who participated in our study interacted meaningfully with e-learning. For educators, the potentials offered by e-learning goes beyond teaching students and enters a realm where other activities such as offering online courses, and workshops among other possibilities become available for all stakeholders. Among other positive outcomes of e-learning is its ability to enhance communication between Iraq and other countries and allow for a critical exchange of views and experiences.